A Study On Cosmetic Virtual Product Purchase In Multiplayer Online Battle Area Games - Yılmaz, Mustafa Atahan (European Scientific Journal, ESJ, 2016)
Video games are definitely one of the fastest growing industry in all kind of digital platforms from computers to mobile phones. Cellular data and wifi connections allow players to link to their virtual life easily wherever they are. Online transactions have transformed video games into bustling online markets. Most of the games now offer variety of virtual products to their gamers within the virtual world. Multiplayer online battle arena or MOBA is one of the newest game models that use the free to play business model which allows users to purchase mostly virtual cosmetic products that have no effect on actual game play. In this study gaming time effects and virtual product involvement are researched in concept of cosmetic virtual product purchase. Players divided into five groups for gaming time from very low to very high while two group for virtual product involvement as interested and uninterested. Also players’ views about purchases are discussed.